2006
DOI: 10.1016/j.gca.2005.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of jarosite [KFe3(SO4)2(OH)6] at pH 2 and 8: Insights from batch experiments and computational modelling

Abstract: Jarosite [KFe 3 (SO 4 ) 2 (OH) 6 ] is a mineral that is common in acidic, sulphate-rich environments, such as acid sulphate soils derived from pyrite-bearing sediments, weathering zones of sulphide ore deposits and acid mine or acid rock drainage (ARD/AMD) sites. The structure of jarosite is based on linear tetrahedral-octahedral-tetrahedral (T-O-T) sheets, made up from slightly distorted FeO 6 octahedra and SO 4 tetrahedra. Batch dissolution experiments carried out on synthetic jarosite at pH 2, to mimic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 34 publications
14
74
2
1
Order By: Relevance
“…As jarosite-minerals are inherently unstable under circumneutral conditions, the significant change in Eh was indicative of a rapid mineral dissolution. The low Fe aq concentrations support prior investigations on jarosite dissolution as Fe(III) exhibits very low solubility at circumneutral pH [8,35,36]. The Ferrozine method showed that all Fe aq was in the form of Fe(II) [37,38].…”
Section: No-bacteria Controls (Ln and Hn)supporting
confidence: 77%
“…As jarosite-minerals are inherently unstable under circumneutral conditions, the significant change in Eh was indicative of a rapid mineral dissolution. The low Fe aq concentrations support prior investigations on jarosite dissolution as Fe(III) exhibits very low solubility at circumneutral pH [8,35,36]. The Ferrozine method showed that all Fe aq was in the form of Fe(II) [37,38].…”
Section: No-bacteria Controls (Ln and Hn)supporting
confidence: 77%
“…2a-c) with those previously reported confirm that the phases synthesised are jarosite analogues and that no other phases have been detected (Baron and Palmer, 1996;Drouet and Navrotsky, 2003;Powers et al, 1975;Serna et al, 1986). The O-H stretching (v OH ) band in the region 2900 to 3700 cm -1 shifts toward lower frequencies for the synthetic Pb-As (3343 cm -1 ), Pb-Cu (3362 cm -1 ) and Pb-Zn jarosites (3357 cm -1 ), compared with end-member synthetic K-jarosite (3385 cm -1 ) (Smith et al, 2006). The synthetic Pb-As jarosite has a relatively low v OH vibration frequency (i.e., 1634 cm -1 ) due to the partial substitution of arsenate for sulphate; arsenate is represented in the spectra as two peaks at 813 and 855 cm -1 (these correspond to the v 1 (AsO 4 3-) and v 3 (AsO 4 3-) modes, respectively, Fig.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 92%
“…Although copiapite and jarosite appear as the minerals with the lowest pH values in the sulphide oxidation pathway (Nordstrom and Alpers, 1999;Smith et al, 2006), this split appears to confirm a higher pH precipitation value for jarosite, suggesting a threshold of pH values detectable in the spectral data. The correlation values (Table II) are only above ≥0.90 for the endmembers for this specific copiapite-alunite assemblage, depicting a strong isolated relationship.…”
Section: Correlation Matrixmentioning
confidence: 89%
“…6 ] form at pH values <3, and precipitate near sources of acidity that are also sources of iron and trace elements (Nordstrom and Alpers, 1999;Smith et al, 2006). However, jarosite may also precipitate at higher pH values of waters, i.e.…”
Section: Correlation Matrixmentioning
confidence: 99%
See 1 more Smart Citation